Copper complexes bearing methylthiophenyl and methylfuranyl derivatives of (R, R)-1, 2-diaminocyclohexane: X-ray structures and catalytic exploitation in Henry reaction. (15th October 2015) - Cho, Jaewon; Lee, Gang Ho; Nayab, Saira; Jeong, Jong Hwa
Graphical abstract: Novel Cu complexes ligated to methylthiophenyl and methylfuranyl derivatives of ( R, R )-1, 2-diaminocyclohexane were synthesized and characterized by X-ray diffraction. The original C 2 -symmetry was lost upon complexation to Cu(II) centre and resulted in selective R, S -coordination of N atoms in case of furanyl containing ligand. The dichloro and diacetato derivatives proved to be active catalysts in asymmetric Henry reaction with moderate yields and enantioselectivities up to 92%. Abstract: Two novel dichloro Cu(II) complexes of ( R, R )- N 1, N 2 -bis((5-methylthiophen-2-yl)methyl)cyclohexane-1, 2-diamine (MTCHD) and ( R, R )- N 1, N 2 -bis((5-methylfuran-2-yl)methyl)cyclohexane-1, 2-diamine (MFCHD) ligands have been synthesised and structurally characterised using X-ray diffraction. The geometry around the Cu(II) centres was distorted square planner. A strong Cu…Ofuranyl interaction exists in Cu(MFCHD)Cl2 that leads to the disappearance of original C 2 -symmetry of the ligand, resulting in selective R, S- coordination of N atoms in (1 R, 2 R )-1, 2-diaminocyclohexane. Catalytic activities of dichloro and diacetato Cu(II) complexes with 3 mol% of i Pr2 NEt were assessed in asymmetric Henry reactions that resulted in moderate to high yields with an enantiomeric excess up to 92%, without air/moisture exclusion.